2014
DOI: 10.15740/has/ijpp/7.2/360-363
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phenyl pyrazole for the managaement of yellow stem borer Scirpophaga incertulas Walker in rice

Abstract: Field experiment was conducted at Banaras Hindu University research farm, Varanasi, on hybrid rice variety PHB 71 during Kharif season of 2012 to study impact of granular formulation of phenyl pyrazole on rice yellow stem borer, Scirpophaga incertulas (Walker). Results revealed that in terms of efficacy against stem borer, overall performance of various spraying insecticidal treatments based on the mean indicated that treatment with Fipronil 0.6 per cent GR @ 60g a.i./ha was the most effective and significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…ha -1 followed by carbosulfan 6G @ 1000 g a.i. ha -1 against the rice yellow stem borer S. incertulas; similar experiment was conducted by Hugar et al (2010). Yadav and Gupta (2020)…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…ha -1 followed by carbosulfan 6G @ 1000 g a.i. ha -1 against the rice yellow stem borer S. incertulas; similar experiment was conducted by Hugar et al (2010). Yadav and Gupta (2020)…”
Section: Resultsmentioning
confidence: 97%
“…In India, S. incertulas has earned the dubious distinction of holding the top position as the most significant pest, as it can attack the rice crop at all stages of its growth (Pasulu et al, 2002;Yadav and Gupta, 2020). The presence of rice stem borers, which infest rice from seedling to maturity, poses a significant obstacle to rice production (Dale, 1994;Hugar et al, 2010;Pathak, 1975). During the vegetative stage, the larvae of Scirpophaga incertulas result in dead hearts, while in the reproductive stage, they lead to the formation of white ear heads (Hugar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Singh et al, (2015), reported about the effectiveness of fipronil 5 SC in reducing the infestation of insect pests in rice. Satyanarayana et al (2014) also studied the efficacy of different granular insecticides against YSB in Varanasi (India) and reported that field performance of the treatments were in the order of fipronil 0.6 GR @ 60 g a.i./ha > fipronil 0.6 GR @ 40 g a.i./ha > cartap HCl 4 GR @ 750 g a.i./ha > fipronil 0.6 GR @ 50 g a.i./ha > fipronil 0.3 GR @ 60 g a.i./ha > carbofuran 3 GR @ 750 g a.i./ha. Dhaka et al (2009) has documented the effectiveness of fipronil against rice stem borer both as foliar application and granular application, due to its systemic activity and persistent toxicity.…”
Section: |7-9|107mentioning
confidence: 99%